Risk Assessment of 5-Chloro-2-Methylisothiazol-3(2H)-One/2-Methylisothiazol-3(2H)-One (CMIT/MIT) Used as a Preservative in Cosmetics - Kim, Min Kook; Kim, Kyu-Bong; Lee, Joo Young; Kwack, Seung Jun; Kwon, Yong Chan; Kang, Ji Soo; Kim, Hyung Sik; Lee, Byung-Mu (Toxicological research (Seoul), 2019)
The mixture of 5-chloro-2-methylisothiazol-3(2H)-one (CMIT) and 2-methylisothiazol-3(2H)-one (MIT), CMIT/MIT, is a preservative in cosmetics. CMIT/MIT is a highly effective preservative; however, it is also a commonly known skin sensitizer. Therefore, in the present study, a risk assessment for safety management of CMIT/MIT was conducted on products containing 0.0015% of CMIT/MIT, which is the maximum MIT level allowed in current products. The no observed adverse effect level (NOAEL) for CMIT/MIT was 2.8 mg/kg bw/day obtained from a two-generation reproductive toxicity test, and the skin sensitization toxicity standard value for CMIT/MIT, or the no expected sensitization induction level (NESIL), was 1.25 µg/cm 2 /day in humans. According to a calculation of body exposure to cosmetics use, the systemic exposure dosage (SED) was calculated as 0.00423 mg/kg bw/day when leave-on and rinse-off products were considered. Additionally, the consumer exposure level (CEL) amounted to 0.77512 µg/cm 2 /day for all representative cosmetics and 0.00584 µg/cm 2 /day for rinse-off products only. As a result, the non-cancer margin of safety (MOS) was calculated as 633, and CMIT/MIT was determined to be safe when all representative cosmetics were evaluated. In addition, the skin sensitization acceptable exposure level (AEL)/CEL was calculated as 0.00538 for all representative cosmetics and 2.14225 for rinse-off products; thus, CMIT/MIT was considered a skin sensitizer when all representative cosmetics were evaluated. Current regulations indicate that CMIT/MIT can only be used at concentrations 0.0015% or less and is prohibited from use in other cosmetics products. According to the results of this risk assessment, the CMIT/MIT regulatory values currently used in cosmetics are evaluated as appropriate.